Pengaruh Pemberian Dosis Poc Jakaba Terhadap Pertumbuhan Vegetatif Tanaman Timun (Cucumis Sativus L.) - Rahmad, Diky; Muryanto, Sigit; Hertini, Etty Sri (AGROTECH Research Journal, 2025)
JAKABA POC from fermented leri water and bamboo roots contains nutrients such as nitrogen, phosphorus and potassium which are needed by plants. The increasing cost of inorganic fertilizers is increasingly becoming a burden on farmers. This research is based on the majority of Indonesian people considering cucumber cultivation only as a side business, even though this plant has good economic potential. The aim of this research was to determine the ability of POC JAKABA to meet nutrient needs and to determine the correct dose of POC JAKABA for the growth of cucumber plants during the vegetative period. This research was carried out in June-July 2024, located in Suyudan Hamlet, Kiringan, Boyolali Regency. The research parameters were plant height, number of leaves, number of branches and number of flowers 7 DAP, 14 DAP, 21 DAP, 28 DAP. The research used a Randomized Block Design (RAK) method consisting of 4 treatments and 3 replications, with treatment T0 = without JAKABA fertilization, T1 = giving JAKABA fertilizer at a dose of 100 ml/plant, T2 = giving JAKABA fertilizer at a dose of 200 ml/plant, T3 = giving JAKABA fertilizer dose 300ml/plant. The results showed a significant effect on plant height at 21 DAP and 28 DAP and group variations showed a significant effect, showed a significant effect on the number of leaves at 21 DAP and 28 DAP and group variations showed a significant effect, showed a significant effect on the number of branches at 21 DAP and 28 DAP and group variations showed a significant effect,, showed a significant effect on the number of flowers at 14, 21 DAP and 28 DAP and group variations showed a significant effect. The conclusion from the results of this research is that giving POC JAKABA is effective in meeting the nutritional and nutrient needs of cucumber plants. The best recommended dose is 200 ml of plant.